Use of the “Satisfaction With Family Life Scale” for Family Environment in Latvia - Dombrovskis, Aivis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This study was conducted to ensure that the family environment research method “Satisfaction with the family live scale” (SWFL) (Agate, Zabriskie, et.al., 2009) can be adapted to Latvia’s circumstances. The research cohort (n=485) was made up of 161 men and 321 women aged 18-21. There were four hypotheses in the study: 1) SWFL should not be correlated with gender and age in the 18-22 age group; 2) SWFL should indicate positive correlation with cohesion in family and 3) negative correlation with conflicts in family 4) Items of instrument must establish one factor. The study analyses the adaptation of the survey and reflects the major results in terms of utilising the survey for scholarly research and practical work in relation to an examination of the family environment in Latvia. Internal compatibility was measured on the basis of the Cronbach alpha (ɑ = 0.86). The results of the research confirm the stated hypotheses and make it possible to conclude that adaptation of the survey was successful. The survey can, therefore, be used under Latvia’s circumstances, as well